Безопасность в польской и русской аксиосферах языкового сознания - Rodziewicz, Barbara (Studia Rossica Posnaniensia, 2021)
In this study, the focus is placed on the semantic content of several concepts in the language consciousness of Polish and Russian speakers revealed by means of the free associative test. Particular attention is paid to the real content of the concepts bezpieczeństwo and безопасность. The paper reports on the results of the comparative analysis of data obtained by means of a free non-directional associative experiment. The distribution of cognitive characteristics according to the degree of brightness in the structure of the concepts is presented. Special attention is paid to identifying similarities and differences in the semantic content and the semantic volume of the investigated concepts. The examined data, taken from associative dictionaries, allow for describing the dynamics of the process of conceptualization as well as for presenting the peculiarities of both concepts. The paper further discusses the formats of the conceptualization of bezpieczeństwo and безопасность and the language dynamics of the objectification of these formats.